A policy mechanism for housing construction activity to achieve social and environmental goals: a case for India - Piyush Tiwari (Intl. Trans. in Op. Res. 11 (2004) 645-665, 2004)
Adequate shelter for all is one of the most pressing challenges faced by developing countries. India is currently facing a shortage of 17.6 million houses. Construction sector represents the most pressing need, viz. shelter. Technologies, which are sustainable environmentally, are another important issue in developing countries, who are on their path to development. Earlier researchers have indicated that construction activity contributes 17 per cent to the carbon dioxide emission in India. In this paper, we have tried to interweave various issues and propose a construction strategy for the Indian housing sector. Affordability of a house and availability of building materials for its construction are the main determinants of access to shelter. This demands efficient use of resources at low cost. This paper analyzes whether it is possible to provide a housing solution at affordable cost by adopting technologies which are less emitting. A policy instrument, energy tax, is designed in this paper that would enforce a switch in technology and promote those technologies, which are well known as least cost but less adopted. An optimization framework developed by Tiwari et al. (1999) and Tiwari (2001) for technology evaluation in house construction based on design codes for India, is used in this paper. Recent government housing policy statements have indicated that an annual supply of two million new houses would be required to meet the current shortage of housing in India. This model is applied to the construction of two million houses. The construction technologies that we evaluate are the commonly used construction technologies as well as the low-cost techniques. It is asserted that by a proper selection of such techniques and material, the costs and emissions can be reduced substantially and at the same time employment can be generated.